1971
DOI: 10.1007/bf00385826
|View full text |Cite
|
Sign up to set email alerts
|

Specificity and reversibility of the rapid stomatal response to abscisic acid

Abstract: Closure of stomata caused by low (10(-7)M) concentrations of abscisic acid (ABA) is specific for cis-trans ABA, and is initiated within 5 minutes. Upon withdrawal of the hormone supply, reopening starts within 5 minutes. Gas analysis of leaves treated with ABA or DCMU allows one to distinguish effects on the stomatal apparatus from inhibition of photosynthesis and to conclude that ABA acts on stomata directly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
38
0
1

Year Published

1972
1972
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(42 citation statements)
references
References 14 publications
3
38
0
1
Order By: Relevance
“…Cummins et al (5) reported that the closing response of stomata caused by applying ABA through the transpiration stream could be reversed if the ABA solution was replaced with water. This reversal did not occur in the experiments reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Cummins et al (5) reported that the closing response of stomata caused by applying ABA through the transpiration stream could be reversed if the ABA solution was replaced with water. This reversal did not occur in the experiments reported here.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that hormonal regulation may be involved in chilling resistance (6,9,15). ABA may aid plants in preserving better water balance (4,7) and in tolerating more chilling stress (8,10). The following reports on water relations and the metabolism of the ABA in corn leaves after mefluidide treatment before, during, and after chilling.…”
mentioning
confidence: 99%
“…Since exogenous application of ABA is known to close stomata (5,9,11), the increased endogenous ABA level that occurs during dehydration may represent an important regulatory mechanism for closing stomata, thereby restricting transpirational water loss (14). Despite this important role for ABA in regulating stomatal aperture, there is little evidence to suggest how its synthesis is triggered or controlled.…”
mentioning
confidence: 99%